Rain erosion fatigue life prediction model for wind turbine coatings : a case study for an offshore wind farm in Northeastern Brazil - PACHECO, Yargo Joseph Duran (2024)
Leading edge erosion by impacting rain droplets and dust particles has a substantial impact on the aerodynamic characteristics and power output of a wind turbine. With the increasing interest in offshore wind farms, with notably higher maintenance costs and greater susceptibility to leading edge erosion, predicting when the coating/protective system will start failing will be crucial for maintenance planning and keeping the power output of the wind turbine at the highest level. Computational models for rain erosion prediction in wind turbine blades are noted in the literature as a promising way to predict the erosion onset of a particular coating under specific environmental conditions. In the present study, a computational model for rain erosion prediction of the leading edge of wind turbine blades has been developed, taking into consideration the turbine power characteristics, coating material features, and raindrop size distribution, which was later combined with an empirically validated finite element analysis. The model was later employed in a case study for a prospective offshore wind farm located off the Northeastern Brazilian coast. First, numerical simulations of rain droplet impacts were conducted in Ansys Explicit Dynamics and validated against real-life experimental results. Then, the offshore wind farm area’s wind and rainfall information were collected from actual satellite observations and climate reanalysis data. Simulations for several droplet diameters, from 0.5 up to 4 mm, impacting an epoxy coating were made, considering the wind turbine’s average operating condition. The impact loads were then used as inputs for a fatigue life prediction model developed in the Python programming language. A sensitivity analysis was performed and shows that the model’s accuracy has a large sensitivity to input data. The resulting impact stress and fatigue damage data were physically consistent. The erosion onset estimates were coherent for most droplet diameters, ranging from 0.46 up to 4.43 years of operating time and consistent with the values found in similar erosion models in the literature. Considering the average rain intensity in the area and its average droplet diameter, the estimated erosion onset is also in agreement with real-life observations in wind turbine blade coatings.